アデリーペンギン ノ ヒ ハンショク コタイ ノ コウゲキセイ ト タマゴ ニ タイスル ハンノウ ニ ツイテ ノ コウサツ - 田宮, 康臣; タミヤ, ヤスオミ; 青柳, 昌宏; アオヤナギ, マサヒロ; Tamiya, Yasuomi; Aoyanagi, Masahiro (1982)
P(論文) アデリーペンギンの非繁殖個体19羽について, その攻撃性と, 人為的に与えた擬卵に対する反応を調べた。1.攻撃性や擬卵に対する反応は個体により異なった。2.一部の個体は抱卵行動を示した。3.巣に擬卵を置くと, 一部の個体の攻撃性は高まった。非繁殖個体には, 未成熟個体と繁殖失敗個体が含まれるが, 本実験において両者を区別することはできなかった。 The aggressiveness of the reoccupying non-breeding Adelie Penguins Pygoscelis adeliae and their response to the eggs placed artificially in their nests were investigated. 1) The aggressiveness and the response to the eggs varied with individuals. 2) Some individuals showed the ability to incubate eggs. 3) After receiving the dummy eggs, some individuals became more aggressive. departmental bulletin paper